Preliminary checklist of Copepoda : Harpacticoida in Western Sarawak waters - Shabdin, Mohd Long; Agatha, Alfred; Norliza, Abdullah (Sarawak Museum Journal, 2005)
The aim of the present study was to establish a preliminary checklist of the harpacticoid copepods species in Sarawak waters. The harpacticoid copepods sampling had been carried out along coastal waters of the western part of Sarawak. A total of 20 families, 42 generaa nd 56 speciesw ere recordedd uring the present study. The change in the particle size composition of sediments in coastal intertidal area of the western part of Sarawak seemst o affect the speciesd istribution of harpacticoidc opepods.